The Eggplant Flower - Mohamad Faizuan, Bin Mat (National Art Gallery, 2019)
The indigenous people are special, they are writers, performers, and artists, and they hail from diverse indigenous communities worldwide. There are approximately around 30 different ethnics at Sarawak. There are Iban, Bidayuh, Melanau, Malay, Bisaya, Orang Ulu, Penan etc. Indigenous people rich with cultural aspects, local knowledge, local beliefs, myths, and legends. However, as they move into 21st century, indigenous people especially in Borneo facing many critical political, economic, social and cultural challenges. One of the greatest challenges for them is that on how to develop model, method, mechanism to capture, maintain, and pass on traditional knowledge system and values to future generations. It is crucial to nurture a genuine understanding towards traditional tribal knowledge. There is undeniably that in some indigenous communities, the original accent and languages, ceremonies, and local knowledge systems have been irretrievably lost. Therefore, through this project by using Iban significant tattoo Bungai Terung is to highlight that tattoo are freely received and given out today in a contemporary society where self-expression in the form of body modification is part of a thriving industry. A very large majority of wearers will get a design based purely on aesthetics, and this unfortunately results in many instances of misapplication of tattoos; misinterpretation, wrong connotations, inappropriate location on the body, demeaning of tribal ritual tattoos and so forth (Christensen W., 2012).